Level of Stress among Institutionalized and Non Institutionalized Elderly Women: A Comparative Study on the Level of Stress among Institutionalized and Non-Institutionalized Elderly Women (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Stress is an emotion which brings a change in ones living. It is needed for survival but the level of stress an individual experience matters for a normal life. It demands a person to get adjusted to the external and internal stressors. Stressors are the factors which lead to stress. They are frustration, pressure and conflict. Stress is a common factor every one of us experience in day to day living. Level of stress is correlated with the developmental stages, living conditions, and many external and biological factors. Stress level may be high among middle aged when compared to old age or vice versa depending upon the predisposing factors of a person’s stress. Levels of stress are always associated with our mental, physical, emotional and social well being. Based on the above idea the present study aims to find out the Level of Stress among elderly women living in Institutionalized and living in family (Non-Institutionalized. Simple random sampling technique was applied to select the sample of 100 elderly women living in Institutions (Old age homes) and 100 elderly women living in Non- Institutions (living in home). An exploratory design was adopted for the study. Personal Stress source inventory developed by Arun k Singh, Ashish K Singh and Aparna Singh along with the Information Schedule prepared by the researcher was used. The obtained results show that Institutionalized and Non Institutionalized elderly Women differ in their Level of Stress.